(untitled) (Revista Contexto & Educação, 2026)
This study aimed to explore the experiences of students in the mathematics learning process mediated by experimental practices. The article begins by acknowledging the challenges faced in teaching this curricular unit, such as the gap between theory and practice, student disinterest, and low performance in national and international assessments. The theoretical framework presents a historical overview of experimentation and discusses recent studies that highlight its pedagogical potential, emphasizing benefits such as stimulating autonomy, collaboration, and the active construction of knowledge. The research, qualitative in approach and basic in nature, was conducted with 19 graduating students from the Integrated High School and Technical Chemistry Course at IFSC – Florianópolis Campus, using an online questionnaire with 17 questions, structured in three blocks. The instrument investigated the participants’ profile, their perceptions of experimentation, the impacts on learning, and the main challenges faced. The data were analyzed based on the Likert Scale and analysis of open-ended questions, discussed individually. The results reveal a predominantly positive perception of experimental practices, associated with increased interest, collaborative learning, better understanding of content, and student motivation. Challenges include difficulties in linking theory and practice, interpreting concepts, and carrying out activities. The study concludes by highlighting the potential of experimentation to make mathematics learning more meaningful and contextualized, and by advocating for the value of pedagogical practices that connect mathematics to students’ reality.